UJI PARAMETER SPESIFIK DAN NON SPESIFIK EKSTRAK ETANOL HERBA MENIRAN (Phyllanthus niruri Linn) - Govan Hanif Sasongko; Adinda Nissa Hardianti; Dewi Cahya Roshiyana; Dian Ayu Irawan; Selvi Putrida (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Phyllanthus niruri Linn is one of the species of the genus Phyllanus that belongs to the herb species with a height of 40–100 cm. It contains chemical compounds such as phyllanthin, hypophyllanthine, niranthin, nirurinethin, norsecurinine, phyllantenol, saponins, flavonoids, polyphenols, philanthine, hypofylanthin, potassium salts. The purpose of this study is to find out the results of specific and non-specific parameter tests as well as the metabolite content of herbal ethanol extract (Phyllanthus niruri L.). Establishing the general standard parameter of the extract is a specific parameter that includes the identity of the extracts, organoleptic extracts, and solute compounds in ethanol solvents & water, whereas non-specific parameters include the drying volume, type weight, and water content. The test results for alkaloids, saponins, tannins, polyphenols, terpenoids, extract yield, ethanol-water soluble essence content, drying loss, specific gravity, water content, total ash content, acid insoluble ash content obtained results that meet standard requirements. In the phytochemical testing of meniran extract, the secondary metabolites contained in the meniran herb were alkaloids, saponins, polyphenols, tannins. In the flavonoid test, the results did not meet the standards due to the evaporation process in the samples taking too long and several environmental factors that influenced the extraction process.